Le potentiel de compétition apparente entre l’orignal (Alces alces) et le caribou forestier (Rangifer tarandus caribou) varie le long d’un gradient latitudinal - Gagné, Caroline (Université Laval, 2014)
Moose benefit from deciduous vegetation that becomes increasingly available during the regeneration of logged forests. This numerical response of moose populations can lead to an increase in gray wolf abundance, which impacts forest-dwelling caribou populations. This study evaluates if the contribution of logging to such apparent competition could vary along the latitudinal axis. We modelled habitat selection behaviour of moose, wolves and caribous monitored by telemetry. After controlling for time since harvest, deciduous vegetation availability decreased with increasing latitude. Moose and wolves avoided cutovers with low deciduous vegetation availability, while they selected harvested stands with high deciduous vegetation availability. Caribou avoided cutovers, and their avoidance increased with the level of deciduous regeneration. The co-occurrence between moose and wolves in cutovers increased with deciduous vegetation availability. Therefore, the contribution of logging to the apparent competition in the moose-wolf-caribou system should be stronger in southern than in northern boreal forest. À la suite d’une coupe forestière, les parterres en régénération peuvent subir un enfeuillement favorable à l’orignal. L’accroissement des populations de loups qui s’en suit affecte alors les populations du caribou forestier. Ce projet vise à évaluer si la contribution de la coupe forestière à cette compétition apparente varie selon un gradient latitudinal. Nous avons modélisé la sélection d’habitat d’orignaux, de loups et de caribous. Après la prise en compte de l’âge de la coupe, l’enfeuillement des parterres diminuait avec la latitude. La sélection des parterres de coupe par les orignaux et les loups augmentait en fonction de leur enfeuillement. Les caribous évitaient les coupes, particulièrement celles riches en feuillus. La cooccurrence de l’orignal et du loup dans les coupes augmente donc en fonction de l’enfeuillement. Ainsi, la contribution de la coupe forestière à la compétition apparente dans le système ...